Incidence of Cardiovascular Events in Hypertensive Patients Based on the Quantity of Major Risk Factors According to the Isfahan Cohort Study - Masoumeh Sadeghi; Reza Shokrani Foroushani; Erfan Sabouri; Mohammad Talaei; Nizal Sarrafzadegan; Shahram Oveisgharan; Erfan Sheikhbahaei; Hamidreza Roohafza (International Journal of Hypertension)
Conclusions: Hypertension alone or combined with other CVD-RFs increases the chance of all-cause mortality, CVD-related mortality, and nonfatal cardiovascular events. Rises in the quantity of other CVD-RFs (specifically to≥ 3) result in highly significant increases in fatal and nonfatal cardiovascular events. Therefore, to reduce mortality and cardiovascular events, hypertensive patients should be thoroughly evaluated for coexisting CVD-RFs, aiming to limit the synergistic effects of multiple CVD-RFs by properly managing modifiable RFs.